THE INFLUENCE OF EMOTIONAL MATURITY AND RELIGIOSITY ON MARRIAGE READINESS IN FATHERLESS WOMEN - Nurwahidah; Wiwik Sulistyaningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the influence of emotional maturity and religiosity on the marriage readiness of fatherless women. The method used was quantitative using a purposive sampling technique totaling 104 respondents. Emotional maturity is measured by the Emotional Maturity Scale, religiosity is measured by the Centrality of religiosity Scale and marital readiness is measured by the Marital Readiness Questionnaire scale. Data analysis used multiple linear regression. The results of the study tested three hypotheses, namely (1) there was a positive influence between emotional maturity on marriage readiness, sig.0.002(p<0.05), R2=0.091, (2) there was a positive influence between religiosity on marriage readiness, sig. 0.000(p<0.05),R2=0.280, (3) emotional maturity and religiosity together have a positive effect on marriage readiness, sig. 0.000(p<0.05) R2=0.324.The higher the emotional maturity and religiosity, the higher the readiness to marry fatherless women. The picture of marriage readiness based on the high fatherless category (inadequate father's involvement) showed low marriage readiness, while the medium category (inconsistent father's involvement) and the low category (adequate father's involvement) showed good marriage readiness.